Roleplay or Vlogging for EFL learners’ speaking skill development? - Seong Hyeon Choi; Kemtong Sinwongsuwat (International Journal of Instruction and Smart Education, 2023)
This study aims to compare the effectiveness of vlogging and role-play in developing different aspects of Thai learners’ English speaking skills. The research participants consisted of 76 university students enrolled in an English conversation course. Divided into 35 pairs, the students were engaged in two task types: five lesson units with role-play and five vlogging tasks. The results showed that both tasks significantly differed in their capacity to maximize each aspect of the speaking abilities assessed. Vlogging assignments appeared to boost clarity of the students’ language use the most compared to their interaction and content. Role-play, on the other hand, elicited their best performance in terms of content and interaction in social activities due to greater opportunities provided for producing and organizing turns with appropriate, meaningful expressions. Further studies should explore different ways to organize and implement each task to maximize its benefits for the development of EFL learners’ speaking skills.